THE ELEMENTS OF VISUAL LANGUAGE AND ITS IMPACT ON DESIGN - Vergara Zurita, Heidy Elizabeth; Rivera Abarca, Ana Lucía; Aguilar Cajas, Héctor Oswaldo; Barreto Bonilla, Jéssica Andrea (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019DO - 10.36779/mktdescubre/v#.#, 2020)
The conceptualization of the visual elements of the image and its impact on the design, together with the composition form the code that allows to transmit ideas, sensations, emotions through messages. In the research methodology, its design is transversal of a non-experimental type, based on a documentary study for the conceptual collection of design elements, using deductive - inductive methods for its analysis and analytical - synthetic to determine the characteristics of each of they. The importance of visual language as one of the communication channels that has used different levels to create representative and symbolic images with different media and resources that adapt to the requirements of both conceptual and visual design, being related to the development of a visual product That reaches the masses and meets the objectives.